Social Protection in Latin America : Achievements and Limitations - Ferreira, Francisco H.G.; Robalino, David (2012)
Social protection systems in Latin America have been transformed in the past two decades. Until the 1980s, those who were not covered by the social security arrangements available primarily in the urban formal sector received little public assistance beyond universal subsidies for some food or fuel purchases. Since the 1990s, the introduction of non-contributory social insurance programs (including "social pensions") and conditional cash transfers has substantially extended the coverage and improved the incidence of social assistance. However, the organic growth of subsidized social assistance in parallel to the older social insurance system, financed largely out of taxes on formal sector employment, has led to a dual system that is neither properly equitable nor efficient. The twin challenges that now face social protection in Latin America are to better integrate those two halves of the system, and to develop programs that promote sustainable self-reliance, by moving from "safety nets" to "opportunity ropes."